WORK SCHEDULING PROGRAM DESIGN FOR LECTURE ATTENDANCE CONTROL AND LECTURER WORKLOAD CALCULATION WITH FINGERPRINT AND RFID IDENTIFICATION DEVICE - M.A. Ade Saputra; Amrifan Saladin Mohruni; Irsyadi Yani (Asosiasi Peneliti Sriwijaya, 2021)
The essential factor in achieving a good learning process is discipline in the lecture process. Students and lecturers are encouraged to be disciplined and active participants in the lecture process, allowing the Lecturer's principal duty of transforming and disseminating science and technology to become more concentrated. Furthermore, to eliminate overlapping lecture schedules, lecture hours, and lecture venues that do not meet needs, it is easier for stakeholders to monitor and regulate lecturers' and students' lecture attendance so that quick and accurate decision-making can be done. To establish discipline in school utilizing biometric identification technology (fingerprints) and Radio Frequency Identification (RFID) technology, developing application software to make it easier to manage work schedules is required. The Work Scheduling program is an online application built with the PHP programming language, MySQL database, and fingerprint and RFID identification support devices that are expected to be effective and efficient tools in the process of scheduling lectures and recording lecture attendance of students and lecturers, making it easier to publish lecture schedules.